Problems of Learning Activities in Modern Education - Mahbubi, M. (International Journal Labs, 2021)
Modern man is a one-dimensional society (one-dimensional man); meaning that all sides of his life are only directed at one goal, namely the sustainability and improvement of the existing system, the system is none other than capitalism. This paper tries to unravel the problems of learning activities in modern education in two perspectives, namely the psychological perspective and the philosophical perspective. This paper used qualitative research method. Western learning theory has dominated and has a great influence in the realm of socio-cultural politics as well as in education. In influencing or dominating education from a psychological perspective, there are at least 4 views on learning theory.